Diversity of Tropical Cyclones Rapid Intensification - Ke Peng; Yu‐Xun Tian; Juan Fang; Yan Liu; Jian‐Feng Gu (Geophysical Research Letters, 2024)
Abstract The study investigates the rapid intensification (RI) of tropical cyclones (TCs) in the Northwestern Pacific. We found that rapid changes in the maximum wind speed (Vmax) and the minimum central pressure (Pmin) are not always concurrent. RI cases can be categorized into three types: (a) RIv, only Vmax strengthens rapidly; (b) RIp, only Pmin decreases rapidly; (c) RIpv, rapid changes in Vmax and Pmin occur concurrently. At the onset of RI, RIv‐type TCs exhibit the weakest intensity and the smallest size, with deep convection concentrated in the inner‐core region; RIp‐type TCs are characterized by the strongest cyclone intensity and the largest outer‐core size, with strong convection covering the inner‐ and outer‐core regions; RIpv‐type TCs show moderate intensity, size, and convection distribution. For RIpv, significant strengthening of wind profile is concentrated in the inner‐core region, while for RIp it is more prominent in the outer‐core.